2016
DOI: 10.1016/j.semcancer.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

F-box protein interactions with the hallmark pathways in cancer

Abstract: F-box proteins (FBP) are the substrate specifying subunit of Skp1-Cul1-FBP (SCF)-type E3 ubiquitin ligases and are responsible for directing the ubiquitination of numerous proteins essential for cellular function. Due to their ability to regulate the expression and activity of oncogenes and tumour suppressor genes, FBPs themselves play important roles in cancer development and progression. In this review, we provide a comprehensive overview of FBPs and their targets in relation to their interaction with the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 247 publications
(204 reference statements)
2
43
0
Order By: Relevance
“…Increase of ROC-1 expression from early to advanced BC, supports its poor prognostic impact and implies a potential role in BC progression. ROC-1 overexpression significant association with desmoplastic stroma was consistent with others supporting the role of ROC-1 as an EMT [17][18][19]. Knockdown of ROC-1 transactivates the RhoA and Rac1 signaling pathways and inhibits mTOR activity, which has a pivotal role in regulation of various cellular processes including EMT, thus causing suppression of EMT in MIBC [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 88%
“…Increase of ROC-1 expression from early to advanced BC, supports its poor prognostic impact and implies a potential role in BC progression. ROC-1 overexpression significant association with desmoplastic stroma was consistent with others supporting the role of ROC-1 as an EMT [17][18][19]. Knockdown of ROC-1 transactivates the RhoA and Rac1 signaling pathways and inhibits mTOR activity, which has a pivotal role in regulation of various cellular processes including EMT, thus causing suppression of EMT in MIBC [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 88%
“…That gene belongs to the same family as FBXO7, a gene mutated in complex parkinsonisms (Di Fonzo et al, 2009;Paisan-Ruiz et al, 2010;Zhao et al, 2013) that is involved in mitochondrial homeostasis and in the ubiquitin ligase complex called SCFs (SKP1-cullin-F-box). FBXO5 is also part of the SCF complex (Randle and Laman, 2016), and our MitoTracker assay showed that FBXO5 induces mitochondrial depolarization upon silencing, suggesting a role of that gene in mitochondrial homeostasis as FBXO7 (Burchell et al, 2013).…”
Section: Discussionmentioning
confidence: 72%
“…Functional FBXO28 activity has also been shown to be associated with adverse breast cancer prognosis, and correlates with TP53 mutation status specifically in ER-positive breast tumors [19, 20]. FBXO28 belongs to the F-box family of proteins that determine the substrate specificity of the SCF ubiquitin ligase complex, a regulatory system that plays a critical role in tumorigenesis [21, 22]. SCF-FBXO28 specifically ubiquitylates Myc, promoting Myc-p300 transcriptional activity and subsequent oncogenic signaling [19].…”
Section: Discussionmentioning
confidence: 99%